Hepatitis B Infection in Microbiology Laboratory Workers: Prevalence, Vaccination, and Immunity Status. (4th December 2012) - Jha, Arun Kumar; Chadha, Sanjim; Bhalla, Preena; Saini, Sanjeev
Abstract : The risk of contracting HBV by health care workers (HCW) is four-times greater than that of general adult population. Studies have demonstrated that vaccine-induced protection persists at least 11 years. High risk groups such as HCWs should be monitored and receive a booster vaccination if their anti-HBsAb levels decrease below 10 mIU/mL. In view of the above this study was undertaken to assess the HBV vaccination of the HCWs and their immunological response. Seventy-two HCWs of the Department of Microbiology, Maulana Azad Medical College, New Delhi, India, were recruited and blood sample was drawn for serological tests (HBSAg, anti-HCV, anti-HBsAb, anti-HBeAb, and anti-HBcAb). Anti-HBs titers of >10 mIU/mL were considered protective. Thirty-four (47.3%) of the participants were completely vaccinated with three doses. 25 (73.5%) of the participants with complete vaccination had protective anti-HBsAb levels as against 8 (53.3%) of those with incomplete vaccination and 9 (39.1%) of those who were not vaccinated at all. One of our participants was acutely infected while 29 participants were susceptible to infection at the time of the study. All HCWs should receive three doses of the vaccine and be monitored for their immune status after every five years. Boosters should be administered to those who become susceptible.